THE IMPLEMENTATION OF COLLEGE PUBLIC DIPLOMACY IN JOHOR BAHRU'S IMMIGRANT CASE HANDLING - Sri Endah Kinasih; Najwa Latifah; Syarifah Hulyatul Umami Alawiyah; Felda Pavita; Yasmin Shafanisa Kamila; Maharani Azzahra; Prismawinda Anifa Nuthqi; Ahmad Zidan Roseno; Raihan Syarif (Universitas Airlangga, 2026)
As migrants who are working abroad, certainly challenges or problems accompany their lives there. Issues including the rights of Indonesian Migrant Workers (PMI), cultural insight, and opportunities to continue their education or work in Indonesia, are a series of common issues faced by PMI in Johor Bahru, Malaysia. This article will discuss the obstacles and challenges faced by PMI as well as present the best solutions for them. The results of this article show that the reality of the problems faced by PMI is quite complex so solving them requires the involvement of all parties, such as the solution discussed by the Airlangga University delegation with the Indonesian Consulate General in Johor Bahru, namely by providing knowledge and skills for PMI as a form of public diplomacy.